Cognitive behavioural therapy in clozapine-resistant schizophrenia (FOCUS): an assessor-blinded, randomised controlled trial. (August 2018) - Morrison, Anthony P; Pyle, Melissa; Gumley, Andrew; Schwannauer, Matthias; Turkington, Douglas; MacLennan, Graeme; Norrie, John; Hudson, Jemma; Bowe, Samantha E; French, Paul; Byrne, Rory; Syrett, Suzy; et al.
Summary: Background: Although clozapine is the treatment of choice for treatment-refractory schizophrenia, 30–40% of patients have an insufficient response, and others are unable to tolerate it. Evidence for any augmentation strategies is scarce. We aimed to determine whether cognitive behavioural therapy (CBT) is an effective treatment for clozapine-resistant schizophrenia. Methods: We did a pragmatic, parallel group, assessor-blinded, randomised controlled trial in community-based and inpatient mental health services in five sites in the UK. Patients with schizophrenia who were unable to tolerate clozapine, or whose symptoms did not respond to the drug, were randomly assigned 1:1 by use of randomised-permuted blocks of size four or six, stratified by centre, to either CBT plus treatment as usual or treatment as usual alone. Research assistants were masked to allocation to protect against rater bias and allegiance bias. The primary outcome was the Positive and Negative Syndrome Scale (PANSS) total score at 21 months, which provides a continuous measure of symptoms of schizophrenia; PANSS total was also assessed at the end of treatment (9 months). The primary analysis was by randomised treatment based on intention to treat, for all patients for whom data were available. This study was prospectively registered, number ISRCTN99672552. The trial is closed to accrual. Findings: From Jan 1, 2013, to May 31, 2015, we randomly assigned 487 participants to either CBT and treatment as usual (n=242) or treatment as usual alone (n=245). Analysis included 209 in the CBT group and 216 in the treatment as usual group. No difference occurred in the primary outcome (PANSS total at 21 months, mean difference −0·89, 95% CI −3·32 to 1·55; p=0·48), although the CBT group improved at the end of treatment (PANSS total at 9 months, mean difference −2·40, −4·79 to −0·02; p=0·049). During the trial, 107 (44%) of 242 participants in the CBT arm and 104 (42%) of 245 in the treatment as usual arm had at least one adverse event (odds ratio 1·09, 95% CI 0·81 to 1·46; p=0·58). Only two (1%) of 242 participants in the CBT arm and one (<1%) of 245 in the treatment as usual arm had a trial-related serious adverse event. Interpretation: At 21-month follow-up, CBT did not have a lasting effect on total symptoms of schizophrenia compared with treatment as usual; however, CBT produced statistically, though not clinically, significant improvements on total symptoms by the end of treatment. There was no indication that the addition of CBT to treatment as usual caused adverse effects. The results of this trial do not support a recommendation to routinely offer CBT to all people who meet criteria for clozapine-resistant schizophrenia; however, a pragmatic individual trial might be indicated for some. Funding: National Institute for Health Research Technology Assessment programme.